Fish Protein Ingestion Induces Neural, but Not Muscular Adaptations, Following Resistance Training in Young Adults - Watanabe, Kohei; Holobar, Aleš; Uchida, Kenji; Mita, Yukiko (Frontiers in Nutrition, 2021)
Purpose: Nutritional supplementation in conjunction with exercise is of interest for the prevention or improvement of declines in motor performances in older adults. An understanding of the effects on both young and older adults contributes to its effective application. We investigated the effect of fish protein ingestion with resistance training on neural and muscular adaptations in young adults using interventions and assessments that have already been tested in older adults. Methods: Eighteen young adults underwent 8 weeks of isometric knee extension training intervention. During the intervention, nine participants ingested 5 g of fish protein (n=9, Alaska pollack protein, APP), and the other nine participants ingested casein as a control (n=9, CAS) in addition to daily meals. Before, during, and after the intervention, the isometric knee extension force, lower extremity muscle mass, and motor unit firing pattern of knee extensor muscles were measured. Results: Muscle strength was significantly increased in both APP and CAS groups from 0 weeks to 4, 6, and 8 weeks of intervention (p < 0.05), but there were no significant differences between the groups. Muscle mass was not significantly changed during the intervention in either group. Significant changes in motor unit firing rates and firing patterns were observed following the intervention in the APP (p < 0.05) but not CAS (p > 0.05) group. Conclusions: These results suggest that dietary fish protein ingestion changes motor unit adaptations following resistance training in young adults, and they differ from the adaptations in older adults.